1989
DOI: 10.1017/s0317167100029899
|View full text |Cite
|
Sign up to set email alerts
|

Progress Report on the Canadian Multicentre Trial of Tetrahydroaminoacridine with Lecithin in Alzheimer's Disease

Abstract: Since the discovery of a significant depletion of acetylcholine in discrete areas of the brain of patients affected by Alzheimer's disease, attempts at symptomatic therapy have concentrated on acetylcholine supplementation, an approach that is based upon the efficacy of dopaminergic supplementation therapy for Parkinson's disease. Choline, then lecithin, used orally, failed to improve symptoms but the hypothesis that long-term choline supplementation might stabilize the course of Alzheimer's disease remains to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…From this it would appear carers were able to detect similar changes as those demonstrated by the MMSE. Similar clinical changes have also been described by Gauthier et al [14], who described an increase in spontaneity of speech and of functional gestures (setting the table, answering the phone) while on THA and a withdrawal of these features during the washout phase. The fact that the mean global score averaged out to the middle of the scale seems to indicate that any observer bias such as the carer's or cli nician's expectations was corrected for in the rating pro cedure.…”
Section: Discussionsupporting
confidence: 82%
“…From this it would appear carers were able to detect similar changes as those demonstrated by the MMSE. Similar clinical changes have also been described by Gauthier et al [14], who described an increase in spontaneity of speech and of functional gestures (setting the table, answering the phone) while on THA and a withdrawal of these features during the washout phase. The fact that the mean global score averaged out to the middle of the scale seems to indicate that any observer bias such as the carer's or cli nician's expectations was corrected for in the rating pro cedure.…”
Section: Discussionsupporting
confidence: 82%
“…The mean duration of disease symptoms was 3.4 ± 0.8 years. The mean pre treatment Mini-Mental State Examination (MMSE) score [18] was 15.5 ± 1.2 (range: [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Subjectsmentioning
confidence: 99%
“…We recruited 38 subjects having a diagno sis of 'probable' or 'definite' AD, as defined by the NINCDS-ADRDA work group in a 9-month clinical trial to test the therapeutic value of THA with lecithin [5]. These pa tients were living at home with GDS scores of 4 and 5, and their caregiver was ques tioned at each visit.…”
Section: Functional Assessment Using An Interviewmentioning
confidence: 99%
“…The use of THA on an experimental basis has opened a door to many drug trials using cognitive enhancing agents, most of them acting on the central cholinergic sys tem. Data from the titration period of the Canadian Collaborative Study on the Use of THA with Lecithin in AD has shown that the RDRS-2 (ADL) is sensitive to drug-related effects: 46 subjects showed a significant im provement between baseline and the dose of 75 mg of THA/day (p = 0.02, Wilcoxon signed-rank test) [5], Data from the double blind phase of that study are currently being analyzed.…”
Section: Functional Assessment In Drug Trialsmentioning
confidence: 99%